Effects on Buildings of Surface Curvature Caused by Underground Coal Mining - Hu, Haifeng; Lian, Xugang; Chen, Shengyun (Journal of Engineering and Technological Sciences, 2016)
Ground curvature caused by underground mining is one of the most obvious deformation quantities in buildings. To study the influence of surface curvature on buildings and predict the movement and deformation of buildings caused by ground curvature, a prediction model of the influence function on mining subsidence was used to establish the relationship between surface curvature and wall deformation. The prediction model of wall deformation was then established and the surface curvature was obtained from mining subsidence prediction software. Five prediction lines were set up in the wall from bottom to top and the predicted deformation of each line was used to calculate the crack positions in the wall. Thus, the crack prediction model was obtained. The model was verified by a case study from a coalmine in Shanxi, China. The results show that when the ground curvature is positive, the crack in the wall is shaped like a âVâ; when the ground curvature is negative, the crack is shaped like a ââ§â. The conclusion provides the basis for a damage evaluation method for buildings in coalmine areas.